Comparison of the Bioeffect of Different Locally Isolated Antifungal Bacteria - ِِAyad Al-Obaidy (مجلة التربية والعلم, 1999)
ABSTRACT Thirteen different soil samples near the rhizosphere were collected from different places in Mosul city/ Iraq. Sixty six different bacterial isolates were isolated from these samples. After testing the capability of each one of these isolates in antagonizing some pathogenic fungi we had 7 different bacterial isolates with an antifungal activities. They were designated as AF1-AF7. An identification of these bacteria was done, and they appeared to belong to different Gram positive and Gram negative bacteria such as Bacillus, Pseudomonas, and Paenibacillus. The antifungal activities of these bacteria were compared between each other on the pathogenic fungi Fusarium, Penicillium, Alternaria, and Aspergillus. The results showed that there is a high probability of isolating different potent antifungal bacteria from the non root-associated soils (and they could be used as potent biological control agent instead of harmful chemicals). The isolates AF3 and AF7 were the most active isolates against the test fungi because of their high inhibition zones and they were belonged to Gram Positive bacteria Paenibacillus and Bacillus respectively, and the inhibition was due to the production of antifungal metabolites or antibiotics.